(untitled) (Journal Of Educational and Psychological Researches, 2024)
the aim of the current research is to identify the role of the teacher in promoting the values of digital citizenship among middle school students in khamis mushait Governorate. To achieve the objective of the research, the descriptive survey approach was used. A scale of 45 items was administered to 358 teachers in the intermediate stage to collect the needed data. The results of the research showed there is a statistically significant difference in the average responses of the study sample on the role of the teacher in promoting the values of digital citizenship among middle school students in school in khamis mushait Governorate, due to the variable of the type of education in which the teacher works, governmental or private, where the difference is clear in favor of teachers who work in private school, as their average ranks are higher, which indicates that they are moving more about the teachers role in promoting the values of digital citizenship among middle school students in khamis mushait Governorate. The results also showed that there are statistically significant differences in the average response ranks of the study sample on the role of the teacher in promoting the values of digital citizenship among middle school students in schools in Khamis Mushait Governorate due to the variable of years of experience in teaching the intermediate stage, i.e., the study sample agreed on the great role of the teacher in promoting the values of digital citizenship among middle school students, as all the values of the average ranks were high. The research recommended developing the teacher’s role in promoting the values of digital citizenship by holding programs, training courses, and workshops that aim to introduce digital citizenship and its importance in protecting the individual and the homeland and achieving digital transformation in educational institutions in line with the Kingdom’s Vision 2030.